Landschapselementen op Limburgse briefhoofden 1850-1960 - Roosen, Joris; Randeraad, Nico (Studies over de sociaaleconomische geschiedenis van Limburg, 2025)
This article explores the use of landscape elements in letterheads from Limburg between 1850 and 1960. Letterheads, initially intended as a business identifier, evolved into a form of direct advertising, particularly for industries, hotels, and shops. With advances in lithography, companies could afford intricate logos and imagery on their correspondence, often showcasing their factories against stylized backdrops. These visual elements, though often overlooked by historians, offer valuable insights into the industrialization and the changing urban landscape of Limburg. This article focuses on how lithography, photography, and abstract representations were used to depict factories, transport infrastructure, and rural surroundings. It highlights the artistic choices in portraying these landscapes to emphasize progress, industrial productivity, and economic optimism.